Analysis of circulating tumour cells separation in a curved microchannel under a high gravitational field. (16th January 2023) - Ayash, Ahmed A.
Graphical abstract: Highlights: A novel micro-analytical device based on using a spinning spiral microchannel is proposed and analysed. A model is developed, giving a quantitative prediction of flow and cells separation inside the channel. The separation of human breast cancer cells from a blood sample has been investigated over a wide range of volume flow rates (100–1000 ml/h) and rotation rates (0–200 rpm). Different than the conventional approaches, the strength and structure of the generated Corilois motions can be adjusted, achieving both higher throughput and complete separation of the cancerous cells. Abstract: Cancer cells can detach from their original place and travel through tiny blood vessels or lymphatic capillaries in nearby tissues, forming a new tumour in other places of the body. While these circulating tumour cells (CTCs) are usually few in relation to the native blood cells, they provide crucial information about the characteristics of the primary tumour. Therefore, detecting and separating such cells from the bloodstream is an essential step in terms of diagnosis, treatment and prognosis of cancer patients. Perhaps, one of the well-known methods of separating CTCs is inertial focusing using a curved microchannel. This approach leaves CTCs separation strongly dependant on the channel design and Reynolds number for a given sample's properties. Thus, the design suitable for a certain sample does not necessarily suit others. Here, a novel micro-analytical device is proposed and analysed. The device is based on using a spiral microchannel spinning around its axis at low rotation speed. The rotation generates Corilois secondary motions, focusing the separation of CTCs. The strength and structure of these Corilois motions can be adjusted easily by changing the rotation rate, which is under external control. This opens up the possibility of handling samples with different properties, achieving both higher throughput and complete separation of CTCs. The present work demonstrates the separation of human breast cancer cells using this approach over a wide range of volume flow rates (100–1000 ml/h) at different rotation rates (0–200 rpm), operating at relatively moderate Reynolds number. A model is developed, giving a quantitative prediction of flow and cells separation. It is shown that, for a single design, the cancer cells can be sorted completely with 100 % purity over a wide range of flow rates (400–700 ml/h) with a small adjustment of the rotation rate.